Supramolecular Structure and Mechanical Properties of Wet-Spun Polyacrylonitrile/Carbon Nanotube Composite Fibers Influenced by Stretching Forces - Mirbaha, Hamideh; Scardi, Paolo; D’Incau, Mirco; Arbab, Shahram; Nourpanah, Parviz; Pugno, Nicola M. (Frontiers in Materials, 2020)
The effect of different elongation conditions on the crystalline structure and physical and mechanical properties of polyacrylonitrile/carbon nanotubes (PAN/CNT) microfibers during wet spinning process was studied. It turns out that the response of polymer chains in PAN/CNT and in PAN fibers to the stretching forces from jet stretching and steam drawing is different. The X-ray diffraction (XRD) results showed that crystalline domain size in steam drawn PAN/CNT fibers is 1.5 times larger than in PAN fibers. CNTs alter the optimum stretching conditions, as they improve the crystalline structure of the PAN/CNT fibers at lower steam drawing ratios than PAN fibers, through nucleation of crystals on their surface. Synchrotron radiation XRD studies revealed that the presence of CNTs improves the crystal orientation of PAN/CNT fibers significantly. In addition, steam drawing is more effective in improving the crystal orientation than jet stretching. Mechanical properties of PAN/CNT fibers have also been affected by steam drawing more than jet stretching. Multi-walled CNTs have the biggest impact on Young’s modulus. The Young’s modulus of PAN/CNT fibers could increase up to 19% higher than PAN fibers at specific stretching conditions, i.e. steam drawing ratio of 2.5. Better orientation of polymers and crystals in fiber direction is the reason for enhancement of Young’s modulus. To our knowledge, the differences between the response of PAN/CNT and PAN fibers to stretching forces inside coagulation bath and after fibers coagulation as well as the difference in evolution of crystalline structure at different stretching stages has not been reported elsewhere.